2007
DOI: 10.1074/jbc.m701013200
|View full text |Cite
|
Sign up to set email alerts
|

On the Oligomeric State of DJ-1 Protein and Its Mutants Associated with Parkinson Disease

Abstract: Mutations in the DJ-1 protein are present in patients suffering from familial Parkinson disease. Here we use computational methods and biological assays to investigate the relationship between DJ-1 missense mutations and the protein oligomeric state. Molecular dynamics calculations suggest that: (i) the structure of DJ-1 wild type (WT) in aqueous solution, in both oxidized and reduced forms, is similar to the crystal structure of the reduced form; (ii) the Parkinson disease-causing M26I variant is structurally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 58 publications
6
29
0
Order By: Relevance
“…Analysis of the crystal structure suggests that the modest thermal destabilization of M26I DJ-1 observed in DSC is due to minor core packing defects created by the branched side chain of I26 and the loss of favorable packing contacts with the C and Sδ atoms of M26. These results are in broad agreement with previous molecular dynamics simulations that showed no major structural changes in response to the M26I missense mutation (61).…”
Section: Dimerization and Secondary Structure Of Dj-1 In Solution Issupporting
confidence: 82%
“…Analysis of the crystal structure suggests that the modest thermal destabilization of M26I DJ-1 observed in DSC is due to minor core packing defects created by the branched side chain of I26 and the loss of favorable packing contacts with the C and Sδ atoms of M26. These results are in broad agreement with previous molecular dynamics simulations that showed no major structural changes in response to the M26I missense mutation (61).…”
Section: Dimerization and Secondary Structure Of Dj-1 In Solution Issupporting
confidence: 82%
“…To this purpose we transfected the PD-associated L166P mutant into siDJ-1#1 cells. L166P protein levels were lower than wt DJ-1, as expected (32). Interestingly, L166P mutant was not able to rescue RET expression as assayed by Western blot (Fig.…”
Section: Dj-1 Wt But Not C106a or Pd-linked L166p Mutants Rescuesmentioning
confidence: 63%
“…Furthermore, recent computational and biochemical studies have shown that M26I dimerizes. 18 Therefore, a common pathological mechanism shared by all mutants is still lacking. Most importantly, as most of the experiments have been performed on the highly unstable L166P protein, more studies are needed on dimer-forming, more stable DJ-1 mutants such as M26I.…”
Section: Discussionmentioning
confidence: 99%
“…Expression vectors encoding for WT, M26I and L166P DJ-1 were described earlier. 18 Two different oligonucleotide sequences were selected for the knockdown TTRAP expression using siRNA Target Finder software (Invitrogen). The hairpin-encoding oligonucleotides were cloned into the pSuperior vector (Invitrogen).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation